Development of electrical power learning video media with project-based learning models - Sucihati Said; Pattaufi Pattaufi; Arnidah Arnidah (Universitas Pendidikan Indonesia, 2025)
Learning at Vocational High Schools, which seems monotonous, requires updates to the learning media so that students can easily understand the material. This research aims to develop learning video media based on Project-Based Learning (PjBL) in the subject of Fundamentals of Electricity Engineering in Vocational Schools. The development model used is the synthesis of three popular models (ADDIE, Four-D, and Borg and Gall) through five stages, namely analyzing the needs and characteristics of students, media design, product development, limited trials, and product evaluation. The video media was developed based on the stages of PjBL, including problem identification, planning, project implementation, and evaluation-reflection. Validation was carried out by material experts and media experts. Practicality and effectiveness were tested through student and teacher response questionnaires and a pretest-posttest. The results showed that the developed media was easy to use and interesting, as evidenced by the increase in students' learning outcomes after using the media. The developed learning media is declared feasible, practical, and effective to support learners' active involvement in project-based learning, improve their concept understanding, and creative thinking skills. Abstrak Pembelajaran pada Sekolah Menengah Kejuruan (SMK) yang terkesan monoton memerlukan pembaruan pada media pembelajaran supaya peserta didik mudah memahami materi. Penelitian ini bertujuan untuk mengembangkan media video pembelajaran berbasis Project-Based Learning (PjBL) pada mata pelajaran Dasar-Dasar Teknik Ketenagalistrikan di SMK. Model pengembangan yang digunakan merupakan hasil sintesis dari tiga model populer (ADDIE, Four-D, dan Borg and Gall) melalui lima tahapan yaitu analisis kebutuhan dan karakteristik peserta didik, perancangan media, pengembangan produk, uji coba terbatas, serta evaluasi produk. Media video dikembangkan berdasarkan tahapan PjBL meliputi identifikasi masalah, perencanaan, pelaksanaan proyek, dan evaluasi-refleksi. Validasi dilakukan oleh ahli materi dan ahli media. Kepraktisan dan efektivitas diuji melalui angket respon peserta didik dan guru serta pretest–posttest. Hasil penelitian menunjukkan bahwa media yang dikembangkan mudah digunakan dan menarik dibuktikan dengan peningkatan hasil belajar peserta didik setelah penggunaan media. Media pembelajaran yang dikembangkan dinyatakan layak, praktis, dan efektif untuk mendukung keterlibatan aktif peserta didik dalam pembelajaran berbasis proyek, meningkatkan pemahaman konsep, dan keterampilan berpikir kreatif mereka. Kata Kunci: ketenagalistrikan; project-based learning; sekolah menengah kejuruan; video pembelajaran